A High-Throughput System for Cyclic Stretching of Precision-Cut Lung Slices During Acute Cigarette Smoke Extract Exposure - Mondoñedo, Jarred R.; Bartolák-Suki, Elizabeth; Bou Jawde, Samer; Nelson, Kara; Cao, Kun; Sonnenberg, Adam; Obrochta, Walter Patrick; Imsirovic, Jasmin; Ram-Mohan, Sumati; Krishnan, Ramaswamy; Suki, Béla (Frontiers in Physiology, 2020)
Rationale: Precision-cut lung slices (PCLSs) are a valuable tool in studying tissue responses to an acute exposure; however, cyclic stretching may be necessary to recapitulate physiologic, tidal breathing conditions. Objectives: To develop a multi-well stretcher and characterize the PCLS response following acute exposure to cigarette smoke extract (CSE). Methods: A 12-well stretching device was designed, built, and calibrated. PCLS were obtained from male Sprague-Dawley rats (N=10) and assigned to one of three groups: 0% (unstretched), 5% peak-to-peak amplitude (low-stretch), and 5% peak-to-peak amplitude superimposed on 10% static stretch (high-stretch). Lung slices were cyclically stretched for 12 h with or without CSE in the media. Levels of Interleukin-1 (IL-1), matrix metalloproteinase (MMP)-1 and its tissue inhibitor (TIMP1), and membrane type-MMP (MT1-MMP) were assessed via western blot from tissue homogenate. Results: The stretcher system produced nearly identical normal Lagrangian strains (E_xx and E_yy, ρ>0.999) with negligible shear strain (E_xy<0.0005) and low intra-well variability 0.1270.073%. CSE dose response curve was well characterized by a four-parameter logistic model (R2=0.893), yielding an IC¬50 value of 0.018 cig/mL. Cyclic stretching for 12 h did not decrease PCLS viability. Two-way ANOVA detected a significant interaction between CSE and stretch pattern for IL-1 (p=0.017), MMP-1, TIMP1, and MT1-MMP (p<0.001). Conclusions: This platform is capable of high-throughput testing of an acute exposure under tightly-regulated, cyclic stretching conditions. We conclude that the acute mechano-inflammatory response to CSE exhibits complex, stretch-dependence in the PCLS.